Evaluation of factors for poor outcome in preterm newborns with posthemorrhagic hydrocephalus associated with late-onset neonatal sepsis - Stevic M; Simic D; Ristic N; Budic I; Marjanovic V; Jovanovski-Srceva M; Repac N; Rankovic-Janevski M; Tasic G (Dove Medical Press, 2018)
Marija Stevic,1 Dusica Simic,1 Nina Ristic,2 Ivana Budic,3 Vesna Marjanovic,3 Marija Jovanovski-Srceva,4 Nikola Repac,5 Milica Rankovic-Janevski,6 Goran Tasic5,7 1Department of Anesthesia, Medical Faculty University of Belgrade, Belgrade, Serbia; 2Department of Gastroenterology, University Children’s Hospital, Belgrade, Serbia; 3Department of Anesthesia, Medical Faculty University of Nis, Nis, Serbia; 4Department of Anesthesia, Medical Faculty University of Skopje, Skopje, Macedonia; 5Clinical Center of Serbia, Institute of Neurosurgery, Belgrade, Serbia; 6Department of the Specialized Care, Institute of Neonatology, Belgrade, Serbia; 7Department of Neurosurgery, Medical Faculty University of Belgrade, Belgrade, Serbia Purpose: Preterm newborns, due to many factors, are at increased risk for poor neural development, intraventricular hemorrhages, infections, and higher rate of mortality. The aim of this study was to evaluate the risk factors associated with poor outcome in preterm neonates with late-onset neonatal sepsis (LONS) who had posthemorrhagic hydrocephalus and underwent neurosurgical procedures for treatment of the hydrocephalus. Patients and methods: Preterm neonates who had undergone insertion of ventriculoperitoneal shunt or Ommaya reservoir, during the 10-year period at University Children’s Hospital, were retrospectively analyzed. According to the presence or absence of LONS, patients were divided into LONS group and non-LONS group. In both groups, we analyzed demographic and clinical data as well as nondependent factors. Additionally, we evaluated the patients who had lethal outcome in respect to all the analyzed factors. Results: A total of 74 patients were included in the study, 35 in LONS group and 39 in control group. Patients in LONS group were born significantly earlier with lower birth weight, needed significantly higher O2 inspiratory concentration, and had longer duration of mechanical ventilation when compared to the nonseptic group. Five patients in LONS group had lethal outcome, and for these patients we identified a grade American Society of Anaesthesiologists score of 4 (P=0.000), ductus arteriosus persistens (P=0.000), bronchopulmonary dysplasia (P=0.003), and pneumothorax (P=0.003) as independent preoperative risk factors for lethal outcome. Conclusion: Neurosurgical procedures are relatively safe in neonates with posthemorrhagic hydrocephalus without LONS after birth. However, if LONS is present, various conditions such as preoperative high grade American Society of Anaesthesiologists score, ductus arteriosus persistens, bronchopulmonary dysplasia, and pneumothorax markedly increase the risk for a lethal outcome after the operation. Keywords: late-onset neonatal sepsis, risk factors, preterm infants, posthemorrhagic hydrocephalus, mortality